When entrepreneurship meets finance and accounting: (non-)financial information exchange between venture capital investors, business angels, incubators, accelerators, and start-ups - Bratfisch, Clara; Riar, Frederik J.; Bican, Peter (International Journal of Entrepreneurial Venturing, 2023)
Building on qualitative data from 53 interviews with different types of investors and start-ups, we study the financial and non-financial information that different investor types demand to monitor their portfolio start-ups' performance during different lifecycle stages, as well as how entrepreneurs generate and furnish the required information. We specifically show in detail how investors, like venture capitalists, incubators, or business angels, mitigate agency conflicts through the exchange of specific financial and non-financial information, both formally and informally. By directly comparing both investor and investee cases, we provide insight into the monitoring methods common among different investor types and start-ups. While investors consider accounting to be an important part of the relationship, some entrepreneurs do not or set their priorities differently. Our study illustrates that accounting not only plays a crucial role in the management of established businesses, but is equally important in entrepreneurial investment settings, as is financial literacy.
CRIS-Team WoS Importer:2023-03-31
Keywords: Kulturelle Vielfalt